Application of micronutrient, plant extract and defense inducer as management strategy against Altenaria leaf spot of tomato - Sibuyi, Rainos (My University, 2022)
Alternaria leaf spot, caused by Alternaria solani is one of the most economically important foliar diseases in tomato production. Its management is mainly based on the application of synthetic fungicides. However, the negative side effects of these fungicides on the environment, human health, and increased pathogen resistance have prompted the identification of alternative control measures. This study was established to develop a management strategy against Alternaria leaf spot based on plant nutrition, application of protective plant extract, and induction of a defense mechanism. The antifungal activities of Monsonia burkeana and nano-zinc and copper micronutrient were first tested under laboratory conditions using a food poisoning assay. Potato dextrose agar was amended with different concentrations of M. burkeana (1, 2, 3, 4, 5 g 100 ml-1), Combined nano zinc and copper micronutrient (0.09, 0.12, 0.18, 0.24, 0.30 ml ℓ-1) and un-amended PDA served as control. Treatments were arranged in a Completely Randomized Design (CRD) replicated four times. Both M. burkeana and Nano-zinc micronutrient significantly (P ≤ 0.05) inhibited the mycelium growth of A. solani when compared to the control. A significant reduction was recorded at 5 g 100 ml-1 and 0.30 ml ℓ-1 for both M. burkeana (32.81 %) and combined nano zinc and copper micronutrient (39.69 %) respectively. Both concentrations were further tested under greenhouse and field micro-plot experiments, in a randomized complete block design (RCBD) replicated four times along with Acibenzolar-S-methyl (ASM) defense inducer to determine their effect on Alternaria leaf spot development and severity. All tested treatments significantly reduced Alternaria leaf spot development and severity under both greenhouse and micro-plot when compared to untreated control. The results of the study demonstrated that M. burkeana, nano-zinc and copper micronutrient, and ASM defense inducer significantly reduce Alternaria leaf spot.
Thesis (M.Sc. Agriculture (Plant Protection)) -- University of Limpopo, 2023
Keywords: Alternaria leaf spot; Alternaria solani; M. burkeana; Combined nano zinc; Copper micronutrient; Acibenzolar-S-methyl (ASM); Alternative management; Alternaria diseases; Alternaria solani; Zinc fertilizers; Tomatoes; Foliar diagnosis